New Frontiers in Clinical Legal Education: Harnessing Technology to Prepare Students for Practice and Facilitate Access to Justice - Francina Cantatore
The increased use of technology in legal practice requires law schools to provide students with effective learning opportunities to prepare them for future practice. Clinical legal education (CLE) provides a suitable framework within which to introduce students to the increased demands of legal practice in the technology age. Skills such as familiarity with online systems and resources, as well as coding skills may prove desirable in future law graduates and could be incorporated successfully within a clinical framework. CLE also provides an opportunity for students to learn about digital disruption in the legal industry and new models of legal practice affecting access to justice. Advances in technology have increased opportunities to provide members of the community with solution centred access to justice initiatives. Awareness of these products and initiatives can add value to law clinics by incorporating technology-based tools to enhance access to justice. This article investigates the current focus on legal technology in Australian CLE programs and considers how legal technology may be incorporated into existing clinical structures at universities in order to: firstly, prepare law students for technology-based practice requirements after graduation; and secondly, to enhance access to justice for clients or partners of university law clinics.